Informal work along the business cycle: Evidence from Argentina - Julien Albertini; Arthur Poirier; Thepthida Sopraseuth (IZA Journal of Development and Migration, 2020)
This article sheds light on the dynamics of the Argentine labor market, using quarterly data from the Argentine Labor Force Survey for the period 2003Q3 to 2020Q1. We examine quarterly transition rates in a four-state model with formal employment, informal employment, unemployment, and nonparticipation. We compute the contribution of each transition rate to fluctuations in unemployment and informality rates. We identify five stylized facts: (i) Nearly 40% of the fluctuations in the unemployment rate involves unemployment ins and outs from/to informal jobs. (ii) More than 40% of the fluctuations in informality rate are driven by the variance of the formalization rate (transition from informal to formal employment). (iii) Non-participation matters for the understanding of unemployment volatility but also for the comprehension of the volatility on informality. (iv) Regarding gender differences: transition involving non-participation matters more in the variance of female unemployment and informality rates than for their male counterparts. (v) The informal sector plays an important role as a stepping stone to formal jobs for both men and women. Our article provides empirical targets to discipline theoretical modeling of labor market dynamics with a sizeable shadow economy.
Keywords: E24; E26; J6; 330; worker flows; informality; unemployment; business cycle; emerging market